Pengukuran Efektifitas Pembelajaran Kewirausahaan Dalam Meningkatkan Minat dan Tindakan Berwirausaha Mahasiswa - Agussalim Rahman; Muhammad Amir (Universitas Hamzanwadi, 2020)
The aims of this study was to determine the effectiveness of entrepreneurship learning in increasing the entrepreneurial interest and actions of students who have taken entrepreneurship courses. Research respondents were 94 students of STIE Tri Dharma Nusantara class AKC-1 and AKC-2 who took Entrepreneurship courses in V semesters (shortterm) 2020 .The research approach is a combination of a quantitative approach and a qualitative approach. In this study, researchers used numerical or numeric data in which respondents' answers were made in the form of a Likert scale. Measurement of the effectiveness of research variables was carried out using descriptive statistical analysis techniques by comparing the actual score against the ideal score against each research indicator. The results of the analysis of the total score of the indicator of the interest in entrepreneurship indicator reached 81.29% so that entrepreneurship learning was very effective in arousing interest in entrepreneurship among students.The indicator for entrepreneurial action which is measured by the presence of entrepreneurial activities of students only reaches a score of 10.28%, which means that entrepreneurial learning is not effective in making students take entrepreneurial actions.